Unusual Patterns in Reported Earnings - Thomas, Jacob K. (The Accounting Review, 1989)
[Carslaw [1988] provides evidence that New Zealand firms may round up earnings when they are just below reference points denoted by N X 10k. He observes more zeros and fewer nines than expected by chance in the second-from-left-most digit for a sample of reported earnings numbers. This study examines COMPUSTAT firms to determine whether reported earnings for U.S. firms follow similar patterns. It also reexamines the expectation model used by Carslaw. While U.S. earnings numbers deviate less from expectations, relative to Carslaw's sample, a number of other interesting patterns are observed. Firms reporting losses exhibit the opposite patterns (fewer zeros and more nines). Analysis of quarterly earnings data reveal similar, though considerably smaller, deviations from expected frequencies. Examination of per share earnings (EPS) suggests that rounding behavior is more prevalent in EPS numbers than it is in earnings numbers. Using an alternative model of expected frequencies, unusually high proportions of EPS numbers divisible by ten cents and five cents are observed for firms reporting profits, but no such deviations are observed for firms reporting losses. Again, quarterly EPS data exhibit the same patterns observed for annual EPS numbers.]